Colour Doppler ultrasound in the management of a case of cranial arteritis. Issue 11 (November 1992) - Williamson, T H; Baxter, G; Paul, R; Dutton, G N
Abstract : Colour Doppler ultrasound allows simultaneous B scan and Doppler imaging and can be employed to determine the velocity of blood flow in the vasculature of the eye and orbit. We describe a case of cranial arteritis (giant cell arteritis) in which serial velocimetry recordings were obtained. At one stage in the disease process no blood flow was detectable in the orbit despite previously reliable recordings. This coincided with a deterioration of the clinical state of the patient as signified by recurrent anterior ischaemic optic neuropathy despite controlled symptomatology and erythrocyte sedimentation rate by prednisolone therapy. Subsequent increase in the immunosuppressive therapy was accompanied by a return of blood flow in the orbit. Colour Doppler ultrasound may prove to be a useful examination technique in the diagnosis and management of cranial arteritis.